2022
DOI: 10.1007/s00784-022-04755-9
|View full text |Cite
|
Sign up to set email alerts
|

Cleansing efficacy of an auto-cleaning toothbrushing device with nylon bristles: a randomized-controlled pilot study

Abstract: Objectives To compare the cleansing efficacy of an auto-cleaning device with nylon bristles (Y-brush®) to that of manual toothbrushing. Materials and methods Twenty probands refrained from oral hygiene for 3 days. Rustogi Modified Navy Plaque Index was assessed before and after (randomized) toothbrushing either with the auto-cleaning device for 5 s per jaw or with a manual toothbrush for a freely chosen time up to 4 min. The clinical investigation was repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The results of the present study agree with a recent pilot RCT on the efficacy of Y-brush compared to manual brushing by Keller et al [ 8 ]. They found that full-mouth plaque reduction was higher with manual toothbrushing than Y-brush used for 5 s. For evaluating the effect of longer brushing with the Y Brush, Keller et al [ 8 ] increased the brushing time from 5 to 15 s per arch. Ten volunteers were willing to participate in this second part of the study (non-blinded, nonrandomized).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study agree with a recent pilot RCT on the efficacy of Y-brush compared to manual brushing by Keller et al [ 8 ]. They found that full-mouth plaque reduction was higher with manual toothbrushing than Y-brush used for 5 s. For evaluating the effect of longer brushing with the Y Brush, Keller et al [ 8 ] increased the brushing time from 5 to 15 s per arch. Ten volunteers were willing to participate in this second part of the study (non-blinded, nonrandomized).…”
Section: Discussionsupporting
confidence: 93%
“…However, a new Y-shaped automatic electric toothbrush (Y-brush) with nylon bristles and with action on each separate arch, has recently been proposed in a pilot RCT [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This disagreement could be due to the difference in the experimental setting, where the clinical study may have a different variety of microbial populations, in addition to patients' perceived instructions, i.e., verbal and visual instructions, which might impact the outcomes. Furthermore, the difference in patients' dexterity could explain the disparity in cleaning outcomes using the brushing method [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…18,25 Regardless of manufacturer and consumer preferences, bristles of different types of nylon are effective in removing debris, bacteria, and biolms from oral tissues. 21,26 Other polymers that can be used to produce bristles are polyethylene (PE) and polypropylene (PP). These are widely available lightweight polymers that can produce bristles at low cost.…”
Section: Introductionmentioning
confidence: 99%
“…18,25 Regardless of manufacturer and consumer preferences, bristles of different types of nylon are effective in removing debris, bacteria, and biofilms from oral tissues. 21,26…”
Section: Introductionmentioning
confidence: 99%